Pengejawantahan Teori Psikoanalitik pada Etika Bisnis - Nur Amalia, Shabrina Rahutami; Hamidah, Hamidah (Universitas Negeri Yogyakarta, 2023)
ABSTACTHow can the unconscious side of managerial style cause the failure of business ethics? So far, discussions about unethical behavior in companies, especially fraud, are often linked to motivational theories that only pay attention to the human side of consciousness. The psychoanalytic theory is one of the well-known theories in explaining the human unconscious not to act unethically. This article aims to review how the manifestation of psychoanalytic theory explains unethical behavior in a business organization which is illustrated through the failure to achieve stakeholder theory. This research contributes to the management accounting by providing a new perspective on ethical violations and fraud from the perspective of human psychology. The results of this research show that the subconscious side of the manager can be manifested in his managerial style and exploiting the loopholes in the stakeholder theory causes ethical failure.Keywords: Psychoanalytic Theory, Business Ethic, Stakeholder TheoryABSTRAKBagaimanakah sisi alam bawah sadar manajerial style dapat menyebabkan kegagalan etika bisnis? Selama ini pembahasan mengenai perilaku tidak etis dalam perusahaan, khususnya fraud, seringkali dihubungkan pada teori-teori motivasi yang hanya memperhatikan sisi consciousness dari manusia. Teori psikoanalitik merupakan salah satu teori yang terkenal dalam menjelaskan sisi unconsciousness manusia untuk tidak berbuat tidak etis. Artikel ini bertujuan untuk mengulas bagaimana manifestasi dari teori psikoanalitik dalam menjelaskan perilaku tidak etis dalam sebuah organisasi bisnis yang digambarkan melalui kegagalan pencapaian teori stakeholder. Penelitian ini berkontribusi pada akuntansi manajemen dengan memberikan perspektif baru atas tindakan melanggar etika dan fraud dari sisi ilmu psikologis manusia. Hasil penelitian menunjukkan bahwa sisi bawah sadar manajer dapat termanifestasi dalam gaya manjerialnya dan dengan memanfaatkan celah pada teori stakeholder menyebabkan kegagalan etika.Kata Kunci: Teori Psikoanalitik, Etika Bisnis, Teori Stakeholder